Measuring the effectiveness of the women entrepreneurship programme, as a training intervention, on potential, start-up and established women entrepreneurs in South Africa - Van Vuuren, Jurie Jansen (University of Pretoria, 2013)
Thesis (DCom (Business Management))--University of Pretoria, 2006.